OFR-76-77 Investigation Of The Various Factors Affecting The Response Of Passive Configuration Track Etch Dosimeters To Working Level Hour Exposure In Radon And Radon Daughter Atmospheres - D. B. Lovett (The National Institute for Occupational Safety and Health (NIOSH), 1976)
The work described in this report was directed toward identifying and devising methods to minimize the previously observed variability between working level hour exposures and the alpha particle track densities resulting on Track Etch films exposed to mine atmospheres containing radon and radon daughters. The disequilibrium between radon and its daughters was shown to directly affect this Track Etch film calibration factor. The wide range of disequilibrium states possible in mine situations amply explains the variability in the previous tests. A file of published mine atmosphere composition data was compiled and was used, along with atmospheric compositions derived from several theoretical models ref the atmospheric behavior, to evaluate the variability of several dosimeter configurations and concepts. A nonlinear, iterative regression analyse; was formulated that successfully predicted working levels to within 8 to 10% from only the alpha particle activities (Rn, RA, and RaC') data such as are obtainable from Track Etch films over a wide range of disequrlibrium conditions. A model expressing atmospheric concentrations as a function of radon source strength, plate out rate factor, ventilation rate and the fractional re-entry by recoil of previously platted-out daughters was derived and used in the regression program in addition to preparing a set of reference tables and graphs showing the disequilibrium behavior of the atmosphere. Other factors that can affect the Track Etch Film response writ considered and shown to he less crutial than the disequilibrium state. The results of a series of exposures of a dosimeter concept fixture in the Denver Mining Research Center radon chamber air presented and discussed.